2002
DOI: 10.1016/s0550-3213(02)00319-x
|View full text |Cite
|
Sign up to set email alerts
|

Some irrational Generalised Moonshine from orbifolds

Abstract: We verify the Generalised Moonshine conjectures for some irrational modular functions for the Monster centralisers related to the Harada-Norton, Held, M12 and L3(3) simple groups based on certain orbifolding constraints. We find explicitly the fixing groups of the hauptmoduls arising in each case.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Theorem 5 was used by Dong-Li-Mason in [79], following an observation of Tuite (cf. [76], and [223][224][225] for broader context), to prove Norton's conjecture for the case that g and h generate a cyclic subgroup of M, and this approach, via twisted modules for V , has been extended by Ivanov-Tuite in [141,142]. Höhn obtained a generalization of Borcherds' method by using a particular twisted module for V to construct a BKM algebra adapted to the case that g is in the class named 2A in [56] -the smaller of the two conjugacy classes of involutions in M -and in so doing established [135] generalized moonshine for the functions T (g,h) with g ∈ 2A.…”
Section: Modularitymentioning
confidence: 99%
“…Theorem 5 was used by Dong-Li-Mason in [79], following an observation of Tuite (cf. [76], and [223][224][225] for broader context), to prove Norton's conjecture for the case that g and h generate a cyclic subgroup of M, and this approach, via twisted modules for V , has been extended by Ivanov-Tuite in [141,142]. Höhn obtained a generalization of Borcherds' method by using a particular twisted module for V to construct a BKM algebra adapted to the case that g is in the class named 2A in [56] -the smaller of the two conjugacy classes of involutions in M -and in so doing established [135] generalized moonshine for the functions T (g,h) with g ∈ 2A.…”
Section: Modularitymentioning
confidence: 99%
“…Although this conjecture has been proven in special cases [15][16][17], the general case is still open. 2 The Generalized Moonshine conjecture was given a physical interpretation by Dixon, Ginsparg and Harvey [24] that was later elaborated upon by Ivanov and Tuite [17][18][19]. They showed that the Norton series f (g, h; τ ) arises naturally as the character in the twisted sector V g of an orbifold of the Monster CFT V by the element g ∈ M, 'twined' by the group element h; in standard CFT language, they can therefore be interpreted as Many of the properties conjectured by Norton can be proved from holomorphic orbifold considerations [15].…”
Section: Generalized Monstrous Moonshinementioning
confidence: 99%
“…In the remainder of this subsection, we illustrate how one of these non-zero twisted twining genera, namely the one associated to g ∈ 2B and h ∈ 8A, can be determined explicitly; the other five cases are completely analogous and are dealt with in Appendix A. Let us work with the conventions that the three permutations (1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23) (24), (3,17,10,7,9) …”
Section: Computation Of the Twisted Twining Characters: An Examplementioning
confidence: 99%
“…Norton's Generalized Moonshine Conjectures [N2] concerning centralizers of the Monster group has yet to be generally proven using either Borcherds' approach or orbifold partition function methods although some progress has recently been made in refs. [H] and [T3], [IT1], [IT2] respectively.…”
Section: Introductionmentioning
confidence: 99%